2007
DOI: 10.1002/ange.200701915
|View full text |Cite
|
Sign up to set email alerts
|

Borcluster‐Kationen: Übergang von planaren zu zylindrischen Strukturen

Abstract: Experimente an massenselektierten Borclustern werden seit mehr als 20 Jahren durchgeführt; [1] erst kürzlich wurde es aber dank der Weiterentwicklung der experimentellen und theoretischen Methoden möglich, Strukturen von Clustern eines weiten Größenbereichs zu bestimmen. Die meisten Eigenschaften von Bor-Anionen wurden von Wang et al. [2,3] Für die endgültige Behandlung wurde die letzte Population des genetischen Algorithmus erneut geometrieoptimiert, allerdings mit der größeren def2-TZVPP [13] -Basis, dem be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 29 publications
0
12
1
2
Order By: Relevance
“…[4,5] However, joint experimental and quantum chemistry studies over the past decade have shown that the anionic boron clusters of up to 24 atoms are planar or quasiplanar, consisting of a peripheral ring characterized by two-center-two-electron (2c-2e) bonds and inner atoms that interact with the peripheral ring through delocalized bonds. [6][7][8][9][10][11][12][13][14][15] The s-and p-electron delocalization in boron clusters gives rise to the concept of aromaticity in these species and rationalizes the stability of the planar or quasiplanar structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4,5] However, joint experimental and quantum chemistry studies over the past decade have shown that the anionic boron clusters of up to 24 atoms are planar or quasiplanar, consisting of a peripheral ring characterized by two-center-two-electron (2c-2e) bonds and inner atoms that interact with the peripheral ring through delocalized bonds. [6][7][8][9][10][11][12][13][14][15] The s-and p-electron delocalization in boron clusters gives rise to the concept of aromaticity in these species and rationalizes the stability of the planar or quasiplanar structures.…”
mentioning
confidence: 99%
“…The spectrum shows four well-defined bands (X, A, B, C) in the low binding energy region and more bands (D, E, F) in the high binding energy region, which are only tentatively labeled because of the poorer signal-to-noise ratios. The vertical detachment energy (VDE) of band X is measured to be 3.69 (7) eV. The relatively sharp X band suggests there are probably only small geometry changes of the cluster upon electron detachment to neutral [B 30 ].…”
mentioning
confidence: 99%
“…Theuseofplanarboronringsasbuildingblocksfordesigning new solid-state materials has been predicted by experimentalists and theoreticians studying gas-phase species. [1][2][3][4] One of these rings, namely the planar B 6 ring was discovered recently in the solid-state phase Ti 7 Rh 4 Ir 2 B 8 , whose crystal structure contains titanium atoms sandwiched between B 6 rings. [5] Recently, isolated TaB 6 Ta species could be found in the gas phase, indicating the ability of this planar B 6 ring to strongly bind to transition metals, even in the gas phase.…”
mentioning
confidence: 99%
“…His research group uses, among other things, mass spectrometry and optical spectroscopy as well as surface‐analytical methods. He recently reported in Angewandte Chemie on the transition from planar to cylindrical structures in boron cluster cations2a and in the European Journal of Inorganic Chemistry on the synthesis, characterization, and quantum‐mechanical calculations of a gold–selenium cluster 2b …”
Section: Awarded…︁mentioning
confidence: 99%